Brief review of classical Effort Estimation models for Software development projects - Bravo-Estrada, Diego (2023)
A critical synthesis on the most representative models for software development project effort estimation is provided. This work is a basis for a discussion about the methodological and practical challenges which entail the effort estimation field, specially in the mathematical/statistical modelling fundamentals, and its empirical verification in the software industry.